Integrating eye care in low-income and middle-income settings: a scoping review - Ling Lee; Aryati Yashadhana; Sarity Dodson; Elise Moo; Tiffany Angelopoulos (BMJ Open, 2023)
Objectives Integrated people-centred eye care has been recommended as a strategic framework for reducing global vision impairment and blindness. The extent to which eye care has integrated with other services has not been widely reported. We aimed to investigate approaches to integrating eye care service delivery with other systems in low resource settings, and identify factors associated with integration.Design Rapid scoping review based on Cochrane Rapid Review and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sources MEDLINE, Embase, Web of Science, Scopus and Cochrane Library databases were searched in September 2021.Eligibility criteria Papers with interventions involving eye care or preventative eye care integrated into other health systems, peer-reviewed in English, conducted in low-income or middle-income countries, and published between January 2011 and September 2021 were included.Data extraction and synthesis Two independent reviewers screened, quality appraised and coded included papers. A deductive–inductive iterative analysis approach was used with a focus on integrating service delivery.Results The search identified 3889 potential papers, of which 24 were included. Twenty papers incorporated more than one intervention type (promotion, prevention and/or treatment), but none included rehabilitation. Most articles involved human resources development yet rarely appeared to be people-centred. The level of integration was associated with building relationships and enhancing service coordination. Integrating human resources was challenged by the need for ongoing support and worker retention. In primary care settings, workers were often already at full capacity, had competing priorities, varying capabilities and limited motivation. Additional barriers included inadequate referral and information systems, poor supply chain management and procurement practices and finite financing.Conclusion Integrating eye care into low resource health systems is a challenging task, compounded by resource limitations, competing priorities and ongoing support needs. This review highlighted a need for people-centred approaches to future interventions, and further investigation into integrating vision rehabilitation services.